My Granny's Great Escape - Strong, Jeremy (London Puffın Books, 2007)
Do you think I should ask him out, Nicholas, or is that a bit forward?' 'GRANNY!' We all stared at her. Dad had to sit down. Nicholas's granny has fallen in love - with the elderly Hell's Angel next door! Yurrrgghhh. Nicholas's dad isn't happy about it - but Granny won't let him get in the way. She has a few tricks up her sleeve . . . and Granny on a motorbike could be a very dangerous thing . . .